Pengaruh Ikatan Diagonal GFRP Pada Hubungan Balok Kolom Pracetak Terhadap Kekuatan Sambungan - Hilmansyah, T.; Parung, H.; Djamaluddin, R. (Civil Engineering Department, Tadulako University, 2021)
Precast system is one of the reinforced concrete construction methods that can be used for development. GFRP-S (Glass Fiber Reinforced Polymer Sheet) is one of material that can be used as materials in precast concrete connections. The research aimed at analysing the strenght and behaviour of the concrete beams on beam-column joint precast with GFRP-S.The research was conducted at the Laboratory of Civil Engineering Structures and Materials Hasanuddin University. Beams dimensions was 15cm x 20cm x 120cm and the column was 45cm x 20cm x 100cm. The testing materials were the precast beams with GFRP-S. The imposition given is monotonic static load in one direction.The results showed that an increase in stiffness of the precast beams with GFRP-S. LSI amounted to 16.64% of the LS. LIS amounted to 31.70% of the LS. The average deflection of LS are 55.05 mm. The average deflection of LSI are 45.89 mm. The average deflection of LIS are 37.60 mm. The models of failure in the precast beams with GFRP-S are rupture failure of GFRP-S.